Tubridge flow diverter alone vs. Tubridge flow diverter and coils for the treatment of intracranial aneurysms: A propensity score matching analysis - Shi, Min; Feng, Yu; Zhang, Cheng-Da; Tang, Qing-Wen; Li, Ze-Jin; Zhao, Wen-Yuan; Zhang, Ting-Bao (Frontiers in Neurology, 2022)
The Tubridge flow diverter (TFD) has been widely used in the treatment of intracranial aneurysms. However, there is still no consensus on whether TFD should combined with coiling. The study was designed to assess the clinical performance of TFD in the treatment of intracranial aneurysms, and compare the efficacy and safety between intracranial aneurysms treated with TFD alone and TFD combined with coiling. In the retrospective study, patients treated with the TFD alone or TFD combined with coiling were included between June 2018 to November 2021. These patients were divided into TFD alone group and TFD combined with coiling group. The patient demographic characteristics, aneurysm characteristics, and treatment outcomes between the two groups were compared. In the current study, 93 consecutive patients (65.6% women and a mean age of 55.9±10.7 years) including 104 aneurysms were treated with TFD. Forty-three patients with 49 aneurysms were treated with TFD alone and 50 patients with 55 aneurysms were treated with TFD combined with coiling. Aneurysms in the TFD combined with coiling group were larger (12.9 ± 8.6 vs 8.7±8.8 mm, P = 0.016) compared with those in the TFD alone group, and aneurysms neck were wider (6.5±3.4 vs 5.5±5.4mm, P=0.285). No significant difference was observed between the two groups in term of perioperative complication rate. During follow-up period, the overall complete occlusion rate was 65.2% at 10.1 ± 7.9 months, with 44.8% at 8.7 ± 7.2 months in the TFD group and 81.1% at 11.3 ± 8.2 months in the TFD combined with coiling group, respectively. TFD combined with coiling can be a safe and effective alternative option for the treatment of complex aneurysm. In this study, TFD combined with coiling showed a higher aneurysm occlusion rate without increasing the periprocedural complications. Give the potential risks of these therapeutic modalities, thus very careful consideration is required on an individual patient basis. In the future, more clinical and basic clinicals are required to determine a role of coils in TFD-treated cases to guide clinical decision.